HUBUNGAN AKUISISI PENGETAHUAN, CIPTA PENGETAHUAN, ALIH PENGETAHUAN, KOMPETENSI PENGEMBANGAN, DAN KINERJA TIM PROYEK PENGEMBANGAN PADA PERUSAHAAN TELEKOMUNIKASI DI INDONESIA - Saharso Saharso (Universitas Nasional, 2021)
In Indonesian telecommunication industry, the service providers have rigorous competition, with complex regulations and high investments. To survive, companies must have organizational capabilities to adapt, innovate, and act dynamically. The companies in this industry require deep external knowledge from outside of the organization to adapt to new technologies and to make new products and services. However, the success percentage of a project in the industry is still low only 39%, globally. This research mainly focuses on the discussion about improvement of team performance in the development projects of the telecommunication operator companies in Indonesia. This research also relates to knowledge acquisition, knowledge transfer, and knowledge creation and their relationship to development competence, to achieve optimal project performance. The hypotheseses were tested using the Structural Equation Modeling (SEM) approach with SmartPLS software. Valid data obtained from 133 respondents of project leaders of telecommunications operator companies in Indonesia.The result shows the significant effects of knowledge acquition, transfer, and creation among them and also towards development competence, moreover development competence towards organizational performance in development project team. This research has given theoretical and managerial contributions to strategic management. All of these will extend and enrich management theories.